Wastewater Surveillance of Mpox during the Summer Season of 2023 in Slovenia - Jan Rožanec; Natalija Kranjec; Ivana Obid; Andrej Steyer; Tjaša Cerar Kišek; Tom Koritnik; Mario Fafangel; An Galičič (MDPI AG, 2024)
Since COVID-19, mpox was the first emerging pathogen to have spread globally in 2022. Wastewater-based surveillance (WBS) has proven to be an efficient early warning system for detecting potential resurgences. This report aims to provide insight into the development and implementation of WBS of mpox in Slovenia and to incorporate the surveillance results into the development of public health interventions. WBS of mpox was conducted during the period from 1 June 2023 to 30 September 2023 at the wastewater treatment plant (WWTP) Ljubljana and WWTP Koper. The selected detection method of the monkeypox virus (MPXV) in the wastewater sample was based on PCR analysis. The implemented laboratory method showed that the sample preparation and concentration method enables a stable procedure for MPXV detection in wastewater samples. The laboratory analysis of wastewater samples from the selected WWTPs did not detect the MPXV during the monitoring period. In the event of MPXV detection in a wastewater sample, targeted public health interventions would be implemented, focusing on increasing awareness among the groups of men who have sex with other men and searching for positive mpox cases. We recommend that the developed system be retained in the case of an emergency epidemiological situation.